Strengthening Healthcare Collaborative Governance: A Novel Framework For Multi-Stakeholder Integration In Regional Health Service Management (Architecture Image Studies, 2026)
This study examines collaborative governance implementation in resource-constrained healthcare systems and develops a contextually-adapted framework for multi-stakeholder integration in regional health service management. Employing qualitative case study design in Bangka Tengah Regency, Indonesia, the research collected data through semi-structured interviews with 45 stakeholders, document analysis, and validation workshops. Thematic analysis identified collaboration barriers and informed framework development. Five fundamental barriers undermine collaborative healthcare governance: imbalanced initial conditions with weak leadership; severe resource constraints (physician ratio 0.70 per 1,000 population, 30% below WHO standards); deficient community participation; transparency deficits; and absent evaluation mechanisms. In response, the research developed the MAMA Model comprising three dimensions: Mutual Understanding (consensus building, trust development, openness), Actualization (facilitative leadership, institutional synergy, empowerment), and Make Benefit Collaboration (effectiveness, equity, innovation, accountability, justice). Validation confirmed theoretical soundness and practical viability, with pilot implementation showing improved relationships (85% of participants), enhanced coordination, and service improvements (34% increase in referral completion, 12-point satisfaction increase). Single-case design limits generalizability; longer-term evaluation needed for sustainability assessment. The model requires contextual adaptation for application beyond Indonesian settings. The MAMA Model provides actionable guidance for policymakers and healthcare administrators to strengthen collaborative governance through systematic diagnosis, prioritization, and intervention design addressing structural, procedural, and relational collaboration dimensions. This research advances collaborative governance theory into healthcare-specific, developing country contexts while providing operationally specific framework addressing power asymmetries and resource constraints characteristic of resource-limited settings.